The Emerging Domain of Cooperating Objects Definitions and Concepts - Marrón, Pedro José; Minder, Daniel; Karnouskos, Stamatis (SpringerBriefs in Cooperating Objects, 2012)
This book provides a classification of current and future applications for the domain of Cooperating Objects. The book has been created with a very strong participation of the industry and taking into account current research trends and industrial roadmaps.